Reading Problems in Grade II Elementary School Students - Gusti Ayu Teristalya Merata Putri; Ni Wayan Rati (Jurnal Ilmiah Sekolah Dasar, 2022)
The low reading ability of low grade students, especially in grade II elementary school students, will lead students to face several obstacles during the learning process. In fact, reading ability is regarded as the key to the success of the learning process. Moreover, all activities at school also require reading abilities. This study was intended to explore the problematic phenomenon of reading in grade II elementary school students. To achieve this goal, this study was conducted by using a qualitative descriptive study design, with the type of descriptive study. This study involved grade II elementary school students with low reading skills as study subjects. The samples of this study were determined by means of a purposive sampling technique. The students selected as the sample were 5 grade II students from each elementary school. Consequently, the total number of test subjects in this study was amounted to 40 students. Moreover, the data of this study were collected by utilizing the triangulation method, including observation, interviews, and document studies. The data collection instruments used in this study were observation sheets, interview guidelines, and documentation study sheets. Furthermore, the data in the study were further analyzed by using thematic analysis techniques. Based on the results of the study, six obstacles were found as the cause of reading problems in grade II elementary school students. Thus, it can be concluded that reading problems in grade II elementary school students are caused by various obstacles.